Modern approach to the treatment of stage IV decubitus ulcers - Aleksandr G. Sonis; Anatolii V. Fomin; Sergei V. Ladonin; Maria Y. Sefedinova; Mariya A. Bezrukova; Denis G. Alekseev (Наука и инновации в медицине, 2020)
Objective a retrospective assessment of the bedsores' features, the optimization of treatment tactics, evaluation of long-term treatment results.